Leakage current elimination for Dickson charge pump with a linear regulator. (June 2017) - Lin, Hesheng; Cao, Hongtao; Chen, Zhirong; Chan, Wing Chun; Lee, Wai Kwong; Zhang, Min
Abstract: In this work, a Dickson-like charge pump has been adopted to obtain 30 V voltage for display driver integrated circuit applications. Meanwhile, an irreversible leakage current path in the traditional Dickson charge pump with a linear regulator is presented. This occurs normally when the regulated voltage level is too small to fully turn on its first auxiliary transistor, and then the first-stage Dickson charge pump is turned on all the time and consumes additional power. Three design technologies have proposed to address the power loss and simulation results have been used to verify the designs. Among them, a simple method, which utilizes the unidirectional conduction characteristic of a diode has been proven to be distinct for power saving and performance keeping by the silicon data. The total power consumption for the light load condition is halved for an input voltage of 2.9 V.